2020
DOI: 10.3389/fneur.2020.00114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repetitive Transcranial Magnetic Stimulation on Pain Management: A Systematic Narrative Review

Abstract: Recently, clinicians have been using repetitive transcranial magnetic stimulation (rTMS) for treating various pain conditions. This systematic narrative review aimed to examine the use and efficacy of rTMS for controlling various pain conditions. A PubMed search was conducted for articles that were published until June 7, 2019 and used rTMS for pain alleviation. The key search phrase for identifying potentially relevant articles was (repetitive transcranial magnetic stimulation AND pain). The following inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 131 publications
2
87
1
4
Order By: Relevance
“…The activity of mesolimbic system-related structures is reduced in patients with chronic pain, and studies have shown that chronic pain is effectively controlled by applying deep brain stimulation to one of the structures in the mesolimbic system [ 78 ]. Applying rTMS or transcranial direct current stimulation (tDCS) to the premotor cortex or primary motor cortex has been reported to be effective in reducing chronic pain [ 79 , 80 , 81 ]. This suggests that stimulation of the brain cortex by rTMS or tDCS may directly or indirectly improve activity of mesolimbic structures and normalize the altered connectivity between affected mesolimbic structures [ 79 , 80 , 81 ].…”
Section: Administration Of Dopaminergic Drugsmentioning
confidence: 99%
“…The activity of mesolimbic system-related structures is reduced in patients with chronic pain, and studies have shown that chronic pain is effectively controlled by applying deep brain stimulation to one of the structures in the mesolimbic system [ 78 ]. Applying rTMS or transcranial direct current stimulation (tDCS) to the premotor cortex or primary motor cortex has been reported to be effective in reducing chronic pain [ 79 , 80 , 81 ]. This suggests that stimulation of the brain cortex by rTMS or tDCS may directly or indirectly improve activity of mesolimbic structures and normalize the altered connectivity between affected mesolimbic structures [ 79 , 80 , 81 ].…”
Section: Administration Of Dopaminergic Drugsmentioning
confidence: 99%
“…Repetitive transcranial magnetic stimulation (rTMS) induces electric currents in the brain using high-frequency stimuli that have a short duration through a strong magnetic field [ 6 ]. At least 1,000 impulses below 1 ms are applied.…”
Section: Reviewmentioning
confidence: 99%
“…At least 1,000 impulses below 1 ms are applied. It has been reported that rTMS is effective not only for neurogenic pain, but also for pain attributable to fibromyalgia syndrome, lumbar pain, and shoulder pain [ 6 ]. The primary motor cortex is the main target of stimulation.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations